2003
DOI: 10.1007/bf03033155
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord blood (HUCB) cells for central nervous system repair

Abstract: Cellular therapy is a compelling and potential treatment for certain neurological and neurodegenerative diseases as well as a viable treatment for acute injury to the spinal cord and brain. The hematopoietic system offers alternative sources for stem cells compared to those of fetal or embryonic origin. Bone marrow stromal and umbilical cord cells have been used in pre-clinical models of brain injury, directed to differentiate into neural phenotypes, and have been related to functional recovery after engraftme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 83 publications
0
25
0
6
Order By: Relevance
“…30 Cell therapy has been described as a promising treatment for certain neurodegenerative diseases, as well as various forms of acute injury to the spinal cord and brain. 31 MSCs or multipotent mesenchymal stem cells (MSCs) may serve as a substrate for regenerative stem cell therapy due to their ability to self renew, differentiate into multiple tissues 32 and immunomodulate. 33 Under certain conditions, stem cells from fresh cord blood are able to differentiate into neurons, microglial cells and astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…30 Cell therapy has been described as a promising treatment for certain neurodegenerative diseases, as well as various forms of acute injury to the spinal cord and brain. 31 MSCs or multipotent mesenchymal stem cells (MSCs) may serve as a substrate for regenerative stem cell therapy due to their ability to self renew, differentiate into multiple tissues 32 and immunomodulate. 33 Under certain conditions, stem cells from fresh cord blood are able to differentiate into neurons, microglial cells and astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A major component of regenerative medicine is stem cell-based therapeutics, which have shown promising therapeutic potential for various types of neurological disorders, including TBI (e.g., 57,58,62,109,130), and have reached limited clinical trials [for review see (43)]. Translating cell therapy for treatment of brain diseases to the clinic has involved testing the safety, efficacy, and mechanisms of action of a variety of transplantable donor cells, including fetal stem cells, cancer-derived neuron-like cells, embryonic stem cells, induced pluripotent stem cells, and adult stem cells, such as umbilical cord blood, bone marrow stromal cells, amnion cells, among others (16,57,58,62,63,74,75,84,87,90,109,130). However, among these various types of stem cells, adult stem cells are of interest, as they circumvent ethical and moral problems and also teratogenic and oncogenic risks usually associated with transplantation of embryonal or fetal-derived stem cells (85).…”
Section: Stem Cell Transplantation In Tbimentioning
confidence: 99%
“…We conducted an analysis of mouse brain homogenates using monoclonal Ab [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] antibody (6E10) to analyze Ab species and b-C-terminal fragments (b-CTFs), from both the 6-and 10-month treated groups. The 6E10 antibody specifically recognizes APP and b-CTFs.…”
Section: Cerebral Parenchymal B-amyloid Plaques Are Reduced In Ad Tramentioning
confidence: 99%
“…Together, these could prevent infiltrating T cells from being activated and thus downregulate proinflammatory secretions [8,45,57]. HUCBC studies done in vitro have shown that these cells secrete soluble factors that have salutary effects [16,58]. Cultured HUCBC supernatants, for example, stimulate survival of neural cells and peripheral blood mononuclear cells cultured under conditions designed to induce cell stress and limit protein synthesis [12].…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation